Association between nontraditional lipid parameters and the risk of type 2 diabetes and prediabetes in patients with nonalcoholic fatty liver disease: from the national health and nutrition examination survey 2017–2020 - Liu, Jierui; Fu, Qingan; Su, Ruolin; Liu, Rixiang; Wu, Shisheng; Li, Ke; Wu, Jianhua; Zhang, Nuobei (Frontiers in Endocrinology, 2024)
Background:Nonalcoholic fatty liver disease (NAFLD) is a prevalent metabolic disorder strongly linked to type 2 diabetes mellitus (T2DM). Understanding the predictive value of lipid parameters in identifying abnormal glucose metabolism in NAFLD patients is crucial for early intervention.Methods:This study analyzed data from the National Health and Nutrition Examination Survey(NHANES) database (2017-2020) involving 1066 NAFLD patients. Participants were categorized into three groups: T2DM (n=414), prediabetes mellitus (pre-DM) (n=507), and normoglycemia (NG) (n=145). Traditional lipid parameters (triglycerides (TG) and high-density lipoprotein cholesterol (HDL-C)) and nontraditional lipid parameters (atherogenic index of plasma (AIP), residual cholesterol (RC), and non-high-density lipoprotein cholesterol (non-HDL-C)) were evaluated for their association with T2DM and pre-DM.Results:Elevated TG levels were significantly associated with an increased risk of T2DM and pre-DM, whereas high HDL-C demonstrated a protective effect. Among nontraditional lipid parameters, increased AIP and RC were most strongly associated with T2DM risk, while high non-HDL-C was best associated with the development of pre-DM. Stratified analyses revealed that these associations were stronger in younger, non-obese, smoking, and female NAFLD patients.Nontraditional lipid parameters, particularly AIP and RC, show superior predictive value over traditional lipid parameters in identifying abnormal glucose metabolism in NAFLD patients. Incorporating these novel biomarkers into clinical practice could enhance early detection and prevention strategies for T2DM and pre-DM in this high-risk population.